2022
DOI: 10.1136/archdischild-2022-324472
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal mask airway versus face mask ventilation or intubation for neonatal resuscitation in low-and-middle-income countries: a systematic review and meta-analysis

Abstract: ObjectiveTo assess whether laryngeal mask airway (LMA) as compared with face mask (FM) or endotracheal intubation (ETT) is more effective in delivering positive pressure ventilation (PPV) during neonatal resuscitation in low-and-middle income countries (LMICs).Study designWe followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and searched Medline (PubMed interphase), Cumulative Index of Nursing and Allied Health Literature, Embase and Cochrane Registry between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A 2018 Cochrane review evaluated five trials comparing the LMA to facemask ventilation and observed with low to moderate quality evidence that LMA use reduced intubation rates [ 6 ]. More recent systematic [ 15 ] and narrative [ 16 ] reviews reached similar conclusions after inclusion of Pejovic et al’s recent large trial [ 17 ], which included over 1100 neonates. In two other meta-analyses, it was similarly concluded that the use of supraglottic airways, including the LMA, in the neonatal population was associated with less failure of PPV than use of the facemask and subsequently decreased ETT requirements [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…A 2018 Cochrane review evaluated five trials comparing the LMA to facemask ventilation and observed with low to moderate quality evidence that LMA use reduced intubation rates [ 6 ]. More recent systematic [ 15 ] and narrative [ 16 ] reviews reached similar conclusions after inclusion of Pejovic et al’s recent large trial [ 17 ], which included over 1100 neonates. In two other meta-analyses, it was similarly concluded that the use of supraglottic airways, including the LMA, in the neonatal population was associated with less failure of PPV than use of the facemask and subsequently decreased ETT requirements [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 69%
“…More recent systematic [ 15 ] and narrative [ 16 ] reviews reached similar conclusions after inclusion of Pejovic et al’s recent large trial [ 17 ], which included over 1100 neonates. In two other meta-analyses, it was similarly concluded that the use of supraglottic airways, including the LMA, in the neonatal population was associated with less failure of PPV than use of the facemask and subsequently decreased ETT requirements [ 15 , 16 ]. Diggikar et al additionally concluded that in low-to-middle income countries, there is no difference in death or moderate-to-severe hypoxic ischemic encephalopathy (HIE) in infants that were given PPV using a neonatal facemask or the LMA [ 15 ].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…A systematic review in Public Health by Najafi et al35 provided a broad overview of the increased incidence spinal cord injuries in LMICs found there is insufficient literature available to draw conclusions on best management practices and patient outcomes 46. Demonstrating that laryngeal mask airway was both safe and preferable to the use of traditional face mask for positive pressure ventilation during neonatal resuscitation in resource-limited settings, the systematic review and meta-analysis from Diggikar et al47 was both rigorous and supported by strict inclusion criteria. Elbaih et al48 showed that teaching a sequen-…”
mentioning
confidence: 99%